Live birth rate, treatment outcomes, and predictor of assisted reproductive technology among infertile couples in Ethiopia: Retrospective cohort Study Design : Live birth rate, treatment outcomes, and predictor of assisted reproductive technology among infertile couples in Ethiopia - Demissie, Dereje; Dadi, Heran Worku; Oladokun, Adesina (Ethiopian Journal of Reproductive Health, 2026)
Background: Invitro fertilization has become a standard procedure with a record of more than 9 million births worldwide. One in every six couples is facing the problem of infertility. This infertility treatment is the only center in Ethiopia. The overall aim of this study was toinvestigates the live birth rate, treatment outcomes, and predictors of assisted reproductive technology among infertile couples in Ethiopia. Methods: A retrospective study at St. Paul’s Hospital Millennium Medical College in Addis Ababa, Ethiopia, used structured checklists and phone interviews to extract data on infertile couples’ outcomes. The study employed binary and multivariable analysis, cox regression, and waiting time analyses to identify two factors. Result: The study found that Ethiopia’s clinical pregnancy rate was 37%, with live birth rates at 26.3%. Factors affecting live birth outcomes included the 5th day of embryo transfer, maternal age between 20-30 years, marital duration of 5-9 years, number of retrieved eggs, and cost of ART procedures. Live birth rates with waiting for ART procedures were 152/1000, 86/1000, and 6/1000 person-years in the first to 3rd years. Factors predicting the likelihood of live birth rate included marital durations of 5-9 years, frozen/thawed embryos, number of embryos transferred, number of retrieved eggs, total cost of ART procedures, and paid ART procedures. Conclusion: In Ethiopia, assisted reproductive technology outcomes for infertile couples are 37% clinical pregnancy and 26.3% live birth, with factors increasing the odds of live birth. Policymakers and health planners should implement tailored interventions to enhance the success and affordability of ART.